Reuse of cooking oil for soap making: Alternative method to promote environmental awarenessand increase the income of poor communities in the municipality of São Mateus/ES - Nery Furlan Mendes, Ana; Chagas da Silveira, Vivian; Pereira Barcellos, Cátia; Mendonça Ambrozim, Flaviane; de Jesus Júnior, Maurino Magno (Guará Journal, 2025)
The incorrect disposal of frying oil causes a negative impact on the environment, because can contaminate the water sources, as well causing hygiene problems and stench. However, it is possible to minimize its polluting effect by producing soap using easily obtainable and not expensive materials. The aim of this work is to convey the processes of recycling of frying oil, through workshops for the production of soap in public schools and associations in São Mateus. The workshops promoted environmental consciousness and also the possibility of provide a new source of income for poor people.